MALDI Imaging of predictive ferritin, fibrinogen and proteases in haemophilic arthropathy - Kriegsmann, Mark; Casadonte, R.; Randau, T.; Gravius, S.; Pennekamp, P.; Strauss, A.; Oldenburg, J.; Wieczorek, Kathrin; Deininger, S.-O.; Otto, M.; Kriegsmann, J. (Haemophilia, 2014)
Arthropathy as a result of repeated joint bleeding is a severe complication in patients with haemophilia. In the evaluation of synovial tissue specimens, histology alone is non-specific and there is considerable morphological overlap with other joint diseases. Formalin-fixed paraffin-embedded specimens are available in pathological institutes and can be studied to understand the pathogenesis of haemophilic arthropathy. A powerful technique to identify hundreds of proteins in a tissue section combining proteomics with morphology is imaging mass spectrometry (IMS). We determined whether matrix-assisted laser desorption/ionization (MALDI) IMS can be used to identify and map protein signatures in the synovial tissue of patients with haemophilic arthropathy. MALDI IMS was applied to synovial tissue of six patients with haemophilic arthropathy. We detected several peaks predictive in mass with ferritin light (m/z 1608) and heavy chain (m/z 1345), alpha- (m/z 1071) and beta (m/z 1274) haemoglobin subunits, truncated coagulation factor VIII peptide (m/z 1502, 1176), beta- and gamma fibrinogen peptides (m/z 980, 1032, 1117 and 1683), and annexin A2 (m/z 1111, 1268, 1460, 2164). In addition, the distribution of these proteins in synovial tissue sections was demonstrated. MALDI IMS identified and mapped specific proteins in the synovial membrane of patients with haemophilic arthropathy known to be involved in the pathogenesis of other joint diseases. This technique is a powerful tool to analyse the distribution of proteins in synovial tissue sections.